San Francisco, Charter for the City 142 (1898) - (:unkn) unknown (My University, 1898)
Every Police Officer shall, upon the arrest of any person charged with the commission of crime, search the person of such offender, and take from him all property and weapons, and forthwith deliver the same to the prison§keeper, who must deliver the same to the Property Clerk, to be by him kept until other disposition be made thereof according to law?
Keywords: PEACE OFFICERS